Paleoclimatic Changes and their Influence on Cultural and Historical Processes during the Neolithic – Eneolitic in the Caspian and Lower Volga Regions - Marianna A. Kulkova; Alexander A. Vybornov (Археология евразийских степей)
The main role in changing of the environment in the semi-desert and steppe zones of Eastern Europe in the Holocene played the precipitation. The first bearers of Neolithic cultures in this territory appeared in the Early Holocene during a transition from wet to arid climatic conditions. The climatic aridization around 6200 cal BC contributed to local population movements and interactions between communities. These processes led to the emergence of new elements in pottery technology and stone industry. The cultural traditions of the Dzhangar and Kairshak types, appeared during the short-term “critical” episode of climate deterioration in the semi-desert zone, continued to develop in the Orlovka culture, formed in the steppe zone of the Lower Volga region. The formation of the Caspian culture, transitional from Neolithic to Chalcolithic, begins about 5500 cal BC in the Northern Caspian. The appearance of syncretic pottery and cattle breeding characterizes this culture. The short-term episodes of climatic aridization, which were followed by periods of humidification, were registered in this time. Eneolithic communities of the Khvalynsk culture, in whose economy appeared copper production together with animal domestication, begin to spread already at the end of a short-term aridization of the climate around 4700 BC in semi-desert and steppe zones.